2014
DOI: 10.18034/abr.v4i1.68
|View full text |Cite
|
Sign up to set email alerts
|

Credit Characteristics and Business Performance: A Survey of Women owned Microenterprises in Tanzania

Abstract: This article provides assessment of the effects of four credit characteristics including size, interest rate, repayment period and borrowing experience on business performance. The article makes use of survey data collected from 217 women microcredit clients from Arusha, Dar es Salaam and Mwanza regions in Tanzania. Bivariate correlation analysis was used to find out specific effect of each of those four credit characteristics on three business performance measures namely total sales revenue, net profit and bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…According to [16], with age, a person's skills and qualifications will increase. [17] argues that the age of women entrepreneurs has a positive and significant effect on the business performance of women entrepreneurs. This is in line with [18] and [19] and contradicts [20] which states that the age of women entrepreneurs has no relationship with business performance.…”
Section: Resultsmentioning
confidence: 99%
“…According to [16], with age, a person's skills and qualifications will increase. [17] argues that the age of women entrepreneurs has a positive and significant effect on the business performance of women entrepreneurs. This is in line with [18] and [19] and contradicts [20] which states that the age of women entrepreneurs has no relationship with business performance.…”
Section: Resultsmentioning
confidence: 99%
“…In a study that examined the empowering effect of microfinance in Tanzania, Kato and Kratzer (2013) report that the members experienced more decision making powers in their households, including control over savings and proceeds from their businesses, improved self-esteem and efficacy. In a different study, Salia and Mbwambo (2014) report significant positive effects on total sales, net profit and ownership of household assets than non-borrowers. Using three measures of enterprise performance, Cooper (2014) noted that women clients experienced increases in average monthly net incomes, increased duration of business operation and creation of jobs for members outside the household.…”
Section: Introductionmentioning
confidence: 88%
“…However, other researchers have pointed out different approaches on dealing with challenges affecting microfinance institution based on their types. As indicated that some microfinance institutions are business based and some are members oriented (community) based kind of financial institution, some are formal and others and informal [16,39,40,41].…”
Section: B Microcredit Programme Of the Village Community Banksmentioning
confidence: 99%
“…In Tanzania, VICOBA and other informal financial institution have reached 27.9% of resources limited societies who have no access to formal bank services [4]. These institutes has almost 19 years of operation since their initiation in year 2000 by CARE Tanzania in Zanzibar and later on Orgut, SEDIT, World Vision and Women in Action (WiA) [40].…”
Section: B Microcredit Programme Of the Village Community Banksmentioning
confidence: 99%